2020
DOI: 10.7759/cureus.9408
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Probiotic Yogurt Consumption on Maternal Health and Pregnancy Outcomes: A Systematic Review

Abstract: The purported benefits of probiotics have been touted as adjunctive or alternative treatment to a variety of diseases. Limited studies have investigated the role of probiotic yogurt in the prevention and management of pregnancy-related adverse events. This literature review aims to analyze the benefits of probiotic yogurt on improving maternal health and pregnancy outcomes and to further identify possible areas of study. A detailed search was conducted utilizing the National Library of Medicine's MEDLINE/PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
(37 reference statements)
1
7
0
1
Order By: Relevance
“…Women were known for dominating the grocery shopping market, and is the sole meal preparer in the household (McGuirt et al, 2018). In addition, yogurt was proven to be good for women's health as it enhances body metabolism, improved infection and inflammatory outcomes of pregnancy and decreasing risk of preterm births (He et al, 2020). The findings also indicated that more than 50% of the respondents were single, consistent with studies by Högskola (2011) and Kusumastuti (2012).…”
Section: Discussionsupporting
confidence: 79%
“…Women were known for dominating the grocery shopping market, and is the sole meal preparer in the household (McGuirt et al, 2018). In addition, yogurt was proven to be good for women's health as it enhances body metabolism, improved infection and inflammatory outcomes of pregnancy and decreasing risk of preterm births (He et al, 2020). The findings also indicated that more than 50% of the respondents were single, consistent with studies by Högskola (2011) and Kusumastuti (2012).…”
Section: Discussionsupporting
confidence: 79%
“…It helps the body to absorb nutrients and enhance immune function by preventing inflammation and stimulating phagocytosis (30). Yogurt is one of the representatives and popular fermented foods worldwide, and consumption of yogurt has been reported to associate with a wide range of health benefits in different populations (31)(32)(33)(34)(35). The potential mechanisms are complicated, but have been identified as producing immunemodulating metabolites, such as short-chain fatty acids (36); preventing pathogens from entering the intestinal epithelium (37); generating antimicrobial compounds (38); producing proteolytic enzymes (39); reducing the fecal enzyme activity of azoreductase, nitroreductase, and b-glucoronidase, which convert the procarcinogens to carcinogens in the colon (40).…”
Section: Introductionmentioning
confidence: 99%
“…Some beneficial effects of probiotic consumption include improvement of digestive system health, reducing the risk of certain cancers, contributing to relief from lactose intolerance symptoms [21][22], enhancement of the immune system, synthesis and enhancement of the bioavailability of nutrients, decreasing prevalence of allergies in susceptible individuals [22], anti-diarrhea effects [21,23] and reducing serum cholesterol [21,[23][24]. In addition, the consumption of probiotic yogurt can also reduce the inflammatory, infectious, and metabolic effects of pregnancy [25]. Among the probiotic bacteria, lactic acid bacteria have been identified as the most important one [26].…”
Section: Introductionmentioning
confidence: 99%